EFEKTIVITAS PUZZLE DRILLING METHOD UNTUK PEMAHAMAN AKUNTANSI DAN SISTEM INFORMASI BAGI UMKM - Ridwan Nurazi; Siti Aisyah; Husaini .; Reza Satria Rinaldi (DHARMA RAFLESIA, 2017)
Point of Sales System (POS System) is a recent popular application that able to overcome the daily business operational problems of SMEs, because it provides information on thetypes of goods, prices, and inventories. This activity introduces POS and training partnersto use the application. These activities are successfully implemented a method that isspecifically designed for the layman who do not understand the science of accounting. Themethod is called puzzle drilling method. This method proved to be effective to change themindset quickly. At first all the partners prepare an income statement with the concept ofmoney going out and money coming, but with this method partners quickly realized theirmisunderstanding and ignorance about the income statement. Generally this activity hasits own benefit for the SMEs owner.Keywords: Point of Sales System, Puzzle Drilling Method, Income Statement